Pemanfaatan Limbah Organik Menjadi Pupuk oleh Pendeta di Lingkungan Gereja: Strategi Pemberdayaan Ekonomi dan Pelestarian Lingkungan - Geovando Siahaan; Asima Putri Handayani Nababan; Yenima Clarisa Simanjuntak; Rina Fretty Manalu; Dedi Endra Tumangger; Jeisa Josua Sinaga; Yustina Romauli Hutasoit; Yusmita Laia (Jurnal Kabar Masyarakat, 2024)
This research aims to analyze strategies for economic empowerment and environmental preservation through the use of organic waste by a pastor in a church environment. This case study focuses on Ibu Ismawati, a widowed priestess with two children, one of whom is studying at college and the other is in high school. Mrs. Ismawati uses her pig manure to produce compost, which is used in small-scale farming on the land behind her house. This agriculture includes corn, chilies, beans, and rice. This research uses a qualitative approach with observation and in-depth interviews to collect data. The research results show that the conversion of organic waste into compost not only helps meet the daily needs of Mrs. Ismawati's family but also supports environmental preservation through waste reduction and increased soil fertility. Additionally, this activity provides a concrete example of how church communities can implement sustainable agricultural practices to improve the economic welfare of their members.